Jute Geotextiles and their Applications in Civil Engineering - Sanyal, Tapobrata; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents a first-of-its-kind exposition on the emerging technology of jute fibre geotextiles. The book covers the characteristics of jute fibre and jute yarns, types and functions of jute geotextiles, and the mechanism of control of surficial soil with jute geotextiles. The content also includes applications such as the mechanisms of functioning of jute geotextiles in strengthening road sub-grade and controlling river bank erosion, stabilization of earthen embankments, management of settlement of railway tracks, and consolidation of soft soil by use of pre-fabricated vertical jute drains (PVJD). Geotextile standards, properties and test methods, variants of jute geotextiles, economical and environmental advantages in different applications are covered along with a few case studies. A chapter on soil basics is included to enable clearer understanding of soil mechanisms. The book can be used as a reference work or as primary or supporting text for graduate and professional coursework. It will also prove useful to researchers and practicing engineers looking for a comprehensive treatise on jute geotextiles.
Chapter I: Introducing Geotextiles -- Chapter II: Jute, Jute Fibre & Jute Yarn -- Chapter III: Jute Geotextiles-Its Types & Functions -- Chapter IV: Soil Basics -- Chapter V: Control of Soil Erosion caused by Rain & Wind with Jute Geotextiles -- Chapter VI: Strengthening of Road Sub-Grade with Jute Geotextiles -- Chapter VII: Controlling River Bank Erosion with Jute Geotextiles -- Chapter VIII: Stabilizing Embankments with Jute Geotextiles -- Chapter IX: Management of Settlement of Railway Tracks -- Chapter X: Consolidation of Soft Soil with Pre-Fabricated Vertical Jute Drain -- Chapter XI: Jute Geotextile Standards, Properties & Test Methods -- Chapter XII: Environmental Aspects -- Chapter XIII: Potentially Important Jute Geo-Textiles -- Chapter XIV: Transportation, Storage and Handling of Jute Geotextiles -- Chapter XV: Prospective Applications of JGT & Its Variants -- Chapter XVI: Economical and Environmental Advantages of JGT in Different Applications -- Chapter XVII: Applications of JGT & Few Case Studies -- Chapter XVIII: Future of Jute Geotextiles -- Bibliography & Index.
Keywords: Engineering geology; Manufactures; Building materials; Geotechnical engineering; Ceramic materials; Geoengineering; Machines, Tools, Processes; Structural Materials; Geotechnical Engineering and Applied Earth Sciences; Building Materials; Ceramics